Pemberian ASI Eksklusif dengan Kejadian Stunting di Wilayah Kerja Puskesmas Kedaton Bandar Lampung - Ratna Susanti; Linawati Novikasari; Setiawati Setiawati (Malahayati Nursing Journal, 2024)
ABSTRACT Stunting is a chronic malnutrition problem that can hinder children's physical and mental development, besides that children are more susceptible to infectious diseases. One of the risk factors for stunting in children is the lack of nutritional intake for toddlers, especially the intake of good nutrition for infants, namely breast milk. Breastfeeding is thought to affect the incidence of stunting. In 2022, the stunting rate in Indonesia reaches 21.6%, and the standard figure set by WHO is 20%. Objective: Known the relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 6 to 59 months in the Working Area of the Kedaton Bandar Lampung Health Center. Known the relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 6 to 59 months in the Working Area of the Kedaton Bandar Lampung Health Center. The type of research used in this study is quantitative, analytical design using a cross sectional approach. The population in the study of toddlers and mothers of toddlers aged 6 to 59 months in the Kedaton Bandar Lampung Health Center Work area as of June 2023 amounted to 50 respondents to data collection techniques using the Non Random Sampling technique accidentally and using the chi square statistical test. Based on the frequency distribution of height of children with stunting 8 (16%) toddlers and not stunting 42 (84%) toddlers, The results of the statistical test obtained a p-value of 0.071 or a p-value of 0.05 with an Odd Ratio of 556 which means that there is a relationship between exclusive breastfeeding and the incidence of stunting in the working area of the Bandar Lampung kedaton health center in 2023. Keywords: Exclusive Breastfeeding, Stunting, Toddlers  ABSTRAK Stunting adalah masalah kurang gizi kronis yang dapat menghambat perkembangan fisik dan mental anak, selain itu anak lebih rentan terhadap penyakit infeksi. Faktor resiko stunting pada anak salah satunya adalah kurangnya asupan gizi balita,terutama asupan gizi tarbaik untuk bayi yaitu ASI. Pemberian ASI diduga berpengaruh terhadap kejadian stunting. Pada tahun 2022 angka stunting diindonesia mencapai 21,6 %, dan angka standar ditetapkan oleh WHO 20%. Diketahui hubungan pemberian ASI Eksklusif dengan kejadian stunting pada balita usia 6 s/d 59 bulan di Wilayah Kerja Puskesmas Kedaton Bandar Lampung. Jenis penelitian yang digunakan dalam penelitian ini adalah kuantitatif, rancangan analitik dengan menggunakan pendekatan cross sectional. Populasi dalam penelitian balita dan ibu balita usia 6 sd 59 bulan  diwilayah Kerja Puskesmas Kedaton Bandar Lampung terhitung sejak bulan juni 2023 yang berjumlah 50 responden teknik pengambilan data menggunakan teknik Non Random Sampling secara accidental dan menggunakan uji statistic chi square. Berdasarkan distribusi frekuensi tinggi badan anak dengan stunting 8 (16%) balita dan tidak stunting 42 (84%) balita, hasil uji statistik didapatkan p-value 0,071 atau p-value 0,05 dengan Odd Ratio 556 yang artinya terdapat ada hubungan antara pemberian ASI Eksklusif dengan kejadian Stunting diwilayah kerja puskesmas kedaton Bandar Lampung tahun 2023. Kata Kunci: ASI Eksklusif, Stunting, Balita